PENGARUH LUAS LAHAN, MODAL, DAN TENAGA KERJA TERHADAP PENDAPATAN PETANI PADI DI DESA SETAIL KECAMATAN GENTENG - Muhammd Zidni Mubarok; Halil; Wicaksono Driyanto Wahyu (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2022)
This study aims to analyze the effect of the independent variables (land area, capital, and labor) on the income (dependent) of rice farmers in Setail Village, Genteng District. The sample used in this study were 97 respondents, using the Slovin formula. This study uses multiple linear regression analysis with SPSS version 22 application. The results showed that the variables of land area and capital have a significant effect on the income of rice farmers, and the labor variable has no significant effect on the income of rice farmers.